Don't just set prices manage them strategically - Nagle, Tom; Kantola Productions; Stanford Video (Mill Valley : Kantola Productions ; Stanford Video, 2005)
Thomas T. Nagle, President, CEO, and founder of Strategic Pricing Group, presents a lecture on the importance of communiction with the customer in setting value-based prices
Lecturer: Thomas T. Nagle
Keywords: Pricing; Marketing -- Management; Marketing -- Decision making; Communication in marketing; Value; Customer relations